Lectures on light nonlinear and quantum optics using the density matrix - Rand, Stephen Colby, 1949- (Oxford : Oxford University Press, 2010)
This book bridges a gap between introductory optics texts and the vanguard of optical science, where light is used as a tool to probe the properties of new materials. A single mathematical tool is introduced that enables readers to understand laser tweezers, laser cooling, optical magnetism, squeezed light, and many other advanced topics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Quantum optics; Nonlinear optics; Density matrices